2016
DOI: 10.7287/peerj.preprints.2615v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyberinfrastructure for an integrated botanical information network to investigate the ecological impacts of global climate change on plant biodiversity

Abstract: ; bthiers@nybg.org. Research in the application of information technology to herbarium management, and outreach efforts to increase access to specimen-based data for the scientific community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 20 publications
0
88
0
Order By: Relevance
“…Most trait data come from Floras and checklists for which annotated information on traits have been extracted, but also large trait compilations with or without spatial context are incorporated (e.g. Enquist et al, 2016;. The range of functional traits currently covered by GIFT reflects different aspects of plant morphology, life history, reproduction, physiology, genetics and ecology (Table S1).…”
Section: Functional Traitsmentioning
confidence: 99%
“…Most trait data come from Floras and checklists for which annotated information on traits have been extracted, but also large trait compilations with or without spatial context are incorporated (e.g. Enquist et al, 2016;. The range of functional traits currently covered by GIFT reflects different aspects of plant morphology, life history, reproduction, physiology, genetics and ecology (Table S1).…”
Section: Functional Traitsmentioning
confidence: 99%
“…Palmer, 2000;Tebaldi & Knutti, 2007), and different species distribution models (SDMs) as well as random subsets of initial distribution data in macroecology (see, e.g. For example, if a macroecologist were to download occurrence data of Carex bohemica for France from BIEN through the BIEN Rpackage (Enquist et al, 2016), she might be happy to find 245 georeferenced observations (Figure 3b). Ensembles in macroecology aim at accessing the uncertainties stemming from a range of variable conditions such as input data, type, structure and complexity of the models, their parameters, or climate scenarios (Dormann et al, 2018 Another source of uncertainty is linked to data: all data sets contain limitations of some sort.…”
Section: Un Certaint Y Propag Ati On and B Ia S In Datamentioning
confidence: 99%
“…Despite such concerns related to geographic coverage and sampling effort, another key challenge is the quality of the data being used (Boyle et al 2013;Enquist et al 2016;Franklin et al 2017). For instance, Wiser (2016) found that a common issue in vegetation plot data bases is incorrect or missing geo-coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Other challenges generally found in large aggregations of occurrence records are related to taxonomic miss-identification and taxonomic shifts (Thessen and Patterson 2011), for which tools have been specifically designed to harmonize naming conventions (Boyle et al 2013). A formal protocol for quality assessment and quality control is still a challenge (Franklin et al 2017), although key recommendations are in place (Costello et al 2014;Enquist et al 2016;Anderson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation